Econometrics of Ascending Auctions by Quantile Regression - Gimenes, Nathalie (The Review of Economics and Statistics, 2017)
This paper suggests an identification and estimation approach based on quantile regression to recover the underlying distribution of bidders’ private values in ascending auctions under the IPV paradigm. The quantile regression approach provides a flexible and convenient parameterization of the private values distribution, with an estimation methodology easy to implement and with several specification tests. The quantile framework provides a new focus on the quantile level of the private values distribution—in particular, the seller’s optimal screening level, which can be very useful for bidders and seller. An empirical application using data from the USFS timber auctions illustrates the methodology.